A rotor ring surface ysz-ba f2 self-lubricating ceramic coating and a preparation method thereof

CN122918487APending Publication Date: 2026-10-16中科骊久(济南)机器人有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611206516.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

(1)基体热损伤问题:传统大气等离子喷涂的焰流温度通常超过8000 ℃,喷涂过程中基体温度往往高于300 ℃,CFRP中的环氧树脂基体在高于150 ℃时即开始分解,导致纤维强度下降,因此,现有喷涂工艺难以直接应用于CFRP基体

Benefits of technology

1.低温制备,避免CFRP基体热损伤:本发明采用LVCS工艺,将喷涂过程中CFRP基体的温度全程控制在150 °C以下,避免了CFRP树脂基体的热分解,保持纤维强度,解决了现有技术中CFRP无法承受高温喷涂的难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918487A_ABST
    Figure CN122918487A_ABST
Patent Text Reader

Abstract

The application discloses a rotor ring surface YSZ-BaF2 self-lubricating ceramic coating and a preparation method thereof, and belongs to the field of aviation thermal spraying technology.The preparation method comprises the following steps: after the surface of the rotor ring is pretreated, supersonic spraying is adopted to sequentially spray a NiCrAlY bonding layer, a NiCrAlY-Al2O3 gradient transition layer, an Al2O3-TiO2 wear-resistant ceramic layer and a YSZ-BaF2 functional layer; the substrate temperature is controlled to be lower than 150 DEG C during the spraying process; then, BaF2-CaF2 eutectic suspension liquid is vacuum-impregnated; and after sintering, polishing is performed.The application realizes the low-temperature preparation of the ceramic coating with high bonding strength, high BaF2 retention rate and wide temperature range self-lubricating performance on the carbon fiber composite material substrate by means of the cooperation of low-temperature spraying and the gradient transition layer, the combination of YSZ coated BaF2 core-shell powder and the post-infiltration process, avoids the thermal damage of the substrate, and meets the aviation use requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aerospace thermal spraying technology, specifically relating to a YSZ-BaF2 self-lubricating ceramic coating on the surface of a rotor ring and its preparation method. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] In the shaftless rotor system of ducted propellers in electric vertical takeoff and landing (eVTOL) aircraft, the rotor rings are typically made of carbon fiber reinforced polymer (CFRP) to achieve extreme lightweight (lift-to-weight ratio ≥6). The outer surface of the rotor rings needs to be coated with a wear-resistant coating to withstand long-term frictional contact with components such as dust brushes and labyrinth seal teeth. This type of coating must simultaneously possess high hardness, wear resistance, chemical inertness, and wide-temperature-range self-lubricating properties.

[0004] From a material functionality perspective, yttrium-stabilized zirconia (YSZ) coatings possess high hardness, wear resistance, and chemical inertness, making them a commonly used ceramic material in thermal barrier coatings for aero-engines. Barium fluoride (BaF2) transforms from brittle to ductile at high temperatures (approximately 400–800 °C) and can be used as a solid lubricant. Therefore, combining YSZ and BaF2 holds promise for obtaining a composite coating (YSZ-BaF2) that combines wear resistance and self-lubricating properties.

[0005] However, when applying the YSZ-BaF2 composite coating to the surface of carbon fiber composite matrix (such as eVTOL rotor rings), it faces three major technical obstacles that have not yet been resolved in the prior art: (1) Substrate thermal damage problem: The flame temperature of traditional atmospheric plasma spraying usually exceeds 8000 ℃, and the substrate temperature during the spraying process is often higher than 300 ℃. The epoxy resin matrix in CFRP begins to decompose when it is above 150 ℃, resulting in a decrease in fiber strength. Therefore, the existing spraying process is difficult to apply directly to CFRP matrix.

[0006] (2) BaF2 volatilization problem at high temperature: BaF2 volatilizes significantly at temperatures above 600 °C. Under the high temperature environment of traditional plasma spraying, BaF2 loss is extremely serious. The BaF2 content in the coating after spraying is far lower than the design value, resulting in insufficient self-lubricating performance of the coating.

[0007] (3) Problem of weak bonding between coating and substrate: CFRP has low surface energy, and the bonding strength between traditional thermal spray coating and substrate is usually less than 20 MPa, which cannot meet the requirements of aviation use.

[0008] Therefore, there is an urgent need for a method to prepare YSZ-BaF2 coatings at low temperatures, while ensuring accurate coating composition, high bonding strength, and excellent thermal shock resistance. Summary of the Invention

[0009] The purpose of this invention is to provide a YSZ-BaF2 self-lubricating ceramic coating on the surface of a rotor ring and its preparation method. By using supersonic spraying (LVCS) combined with a gradient transition layer design and a BaF2 coating-post-infiltration process, the problems of thermal damage, component volatilization and weak adhesion of the CFRP matrix are solved.

[0010] To achieve the above objectives, the present invention is implemented through the following technical solution: In a first aspect, the present invention provides a YSZ-BaF2 self-lubricating ceramic coating on the surface of a rotor ring, comprising, from the inside out: Adhesive layer: NiCrAlY, thickness 0.08-0.12 mm; Gradient transition layer: NiCrAlY-Al2O3, thickness 0.15-0.25 mm; Wear-resistant ceramic layer: Al2O3-13%TiO2, thickness 0.25-0.35 mm; Functional layer: YSZ-BaF2, thickness 0.05-0.10 mm, BaF2 content 15-25 wt%.

[0011] Secondly, the present invention provides a method for preparing a YSZ-BaF2 self-lubricating ceramic coating on the surface of a rotor ring, the method comprising the following steps: (1) Pretreatment: The outer surface of the rotor ring is roughened by grinding, and the roughness Ra reaches 3.2-6.3 μm. It is then ultrasonically cleaned with acetone for 15-25 min to remove surface oil and release agent, and dried at 80-100 °C for 1-2 h. (2) Adhesive layer spraying: NiCrAlY is sprayed onto the surface of the rotor ring after the pretreatment in step (1); (3) Gradient transition layer spraying: NiCrAlY-Al2O3 is sprayed onto the surface of the adhesive layer in step (2); (4) Spraying of wear-resistant ceramic layer: Al2O3-13%TiO2 is sprayed on the surface of the gradient transition layer in step (3), and the surface is roughened after spraying, with the roughness Ra reaching 1.6-3.2 μm; (5) Functional layer spraying: YSZ-BaF2 composite powder is sprayed onto the surface of the wear-resistant ceramic layer in step (4). The YSZ-BaF2 composite powder adopts a coating structure: the surface of BaF2 micro powder is coated with a 2-4 μm thick YSZ shell layer, with a coating rate of >90%; (6) Post-treatment with BaF2: After vacuum impregnation of the sprayed rotor ring, sintering, cooling and polishing are performed until the roughness Ra < 0.8 μm, followed by pore sealing.

[0012] Furthermore, the spraying process in steps (2), (3), (4), and (5) all adopts supersonic spraying, with the following process parameters: the fuel gas is propane + oxygen, the propane flow rate is 3.5-4.5 L / min, the oxygen flow rate is 12-15 L / min; the spraying distance is 100-140 mm; the powder feeding rate is 15-25 g / min; the compressed air cooling pressure is 0.5-0.7 MPa; 4-6 nozzles are evenly distributed in the circumference, and the nozzles are 50-80 mm away from the substrate surface; the substrate is preheated by infrared heating to 70-90 ℃.

[0013] Furthermore, in step (3), the gradient transition layer includes 3-5 sublayers, and the NiCrAlY content gradually changes from 80-90wt% near the substrate to 10-20wt% near the surface along the coating thickness direction. The gradient transition layer achieves the gradual change of composition through a multi-hopper powder feeding system. The NiCrAlY content change gradient between adjacent sublayers is 15-25wt%, and the substrate temperature is controlled to be <120℃ during the spraying process.

[0014] Furthermore, in step (4), the substrate temperature is controlled to be <130°C during the spraying process.

[0015] Furthermore, in step (5), the YSZ-BaF2 composite powder is prepared by sol-gel method or chemical vapor deposition method, and the substrate temperature is controlled to be <150℃ during the spraying process.

[0016] Furthermore, the sol-gel method employs the following approach: (1) Using BaF2 micro powder as the core, it was impregnated and gelled in an alcoholic solution of ZrOCl2·8H2O and Y(NO3)3·6H2O; (2) After sintering at 500-600℃, a YSZ shell layer is formed on the surface of BaF2 micro powder to obtain a composite powder of BaF2 coated with YSZ.

[0017] Furthermore, the chemical vapor deposition method employs the following approach: (1) BaF2 micro powder is placed in a fluidized bed reactor, ZrCl4 and YCl3 are used as precursors, and O2 is used as the reaction gas, and chemical vapor deposition is carried out at 450℃. (2) A YSZ shell is formed on the surface of BaF2 micro powder to obtain a composite powder of BaF2 coated with YSZ.

[0018] Furthermore, in step (6), the impregnation is carried out using a suspension formed by mixing BaF2-CaF2 eutectic powder and ethanol as the impregnating agent. The mass ratio of BaF2 to CaF2 in the BaF2-CaF2 eutectic powder is 62:38, the particle size is 10-20μm, and the solid content of the suspension is 30-40%.

[0019] Furthermore, the sintering in step (6) is carried out under a vacuum or argon protective atmosphere, with a sintering temperature of 800-850 ℃ and a heating rate of 100-150 ℃ / h to prevent the coating from cracking.

[0020] Furthermore, the sealing treatment in step (6) uses silicone resin or polysiloxane sealing agent and is cured at 80-100 ℃ for 2-4 h to improve the corrosion resistance of the coating.

[0021] The beneficial effects of the technical solution provided by this invention are: 1. Low-temperature preparation to avoid thermal damage to the CFRP matrix: The present invention adopts the LVCS process to control the temperature of the CFRP matrix below 150 °C throughout the spraying process, thereby avoiding the thermal decomposition of the CFRP resin matrix, maintaining fiber strength, and solving the problem that CFRP cannot withstand high-temperature spraying in the prior art.

[0022] 2. High BaF2 content ensures self-lubricating performance: This invention uses "YSZ coating of BaF2 core-shell powder + LVCS low-temperature spraying + vacuum impregnation of BaF2-CaF2 eutectic followed by infiltration" to achieve an actual BaF2 content of 85-95% in the coating, which significantly improves the utilization rate of BaF2 and ensures stable self-lubricating performance of the coating in a wide temperature range.

[0023] 3. High bonding strength, solving the problem of easy peeling of CFRP surface coating: The present invention designs a NiCrAlY-Al2O3 composition gradient transition layer, which effectively alleviates the thermal expansion mismatch between YSZ and CFRP, and at the same time enhances the mechanical interlocking between the coating and the substrate. The measured bonding strength of the coating is >40 MPa, which far exceeds the bonding strength of CFRP surface coating in the prior art and meets the strict requirements of aerospace applications.

[0024] 4. Excellent thermal shock resistance, adaptable to drastic temperature changes: Due to the gradient transition layer alleviating thermal stress and the post-treatment reducing coating porosity, the thermal shock resistance of the coating of this invention is significantly improved, reaching 500 °C. The water-cooled thermal shock cycle test results all exceeded 50 cycles without peeling. Attached Figure Description

[0025] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0026] Figure 1 This is a schematic diagram of the coating structure in Example 1; Figure 2 The images are scanning electron microscope (SEM) images of the coatings in Example 1 and Comparative Example 1, where (a) is a cross-sectional morphology image of the coating in Comparative Example 1 and (b) is a cross-sectional morphology image of the coating in Example 1. Figure 3 The EDS elemental distribution and energy spectrum of the wear track region are shown, where (a) is the Al elemental distribution; (b) is the Y elemental distribution; (c) is the Ba elemental distribution; (d) is the F elemental distribution; and (e) is the EDS energy spectrum. Detailed Implementation

[0027] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0028] In all embodiments of this invention, LVCS spraying is used, with a spraying temperature <150 ℃. The specific spraying process parameters are as follows: fuel gas: propane flow rate 4.0 L / min, oxygen flow rate 13.5 L / min; spraying distance 120 mm; powder feeding rate 20 g / min; circumferential cooling with compressed air during spraying: pressure 0.6 MPa, 6 nozzles evenly distributed in the circumference; substrate preheating is achieved by infrared heating to 80°C.

[0029] Example 1 This embodiment provides a low-temperature preparation method for a YSZ-BaF2 self-lubricating ceramic coating on the surface of a rotor ring. The rotor ring substrate is a T800 carbon fiber / epoxy resin composite material with an outer diameter of 800 mm and a wall thickness of 15 mm.

[0030] (1) Surface pretreatment of the matrix: The outer surface of the carbon fiber composite rotor ring is roughened by grinding until the surface roughness Ra=5 μm. Then, it is ultrasonically cleaned with acetone for 20 min to remove surface oil and release agent, and then dried at 90 °C for 1.5 h.

[0031] (2) Adhesive layer spraying: NiCrAlY is sprayed on the pretreated rotor ring surface using LVCS process. The spraying thickness is 100 μm, and the substrate temperature is controlled to be <110 °C during the spraying process.

[0032] (3) Gradient transition layer spraying: Using the LVCS process, a gradient transition layer is sprayed onto the surface of the adhesive layer. The gradient transition layer consists of four sublayers, each with a thickness of 50 μm, for a total thickness of 200 μm. The substrate temperature is controlled to be <110 °C during the spraying process. The composition of each sublayer along the coating thickness direction is as follows: Sublayer 1 (close to the matrix): NiCrAlY 85wt%, Al2O3 15wt%; Sublayer 2: NiCrAlY 60wt%, Al2O3 40wt%; Sublayer 3: NiCrAlY 35wt%, Al2O3 65wt%; Sublayer 4 (near the surface): NiCrAlY 15wt%, Al2O3 85wt%.

[0033] (4) Spraying of wear-resistant ceramic layer: Al2O3-13%TiO2 composite ceramic powder is sprayed on the surface of the gradient transition layer using LVCS. The Al2O3-13%TiO2 composite ceramic powder is a commercially available finished powder for thermal spraying. The spraying thickness is 300 μm. During the spraying process, the substrate temperature is controlled to <120 °C. After the spraying is completed, the surface of the wear-resistant ceramic layer is roughened to make the surface roughness Ra=2.5μm.

[0034] (5) Functional layer spraying: YSZ-BaF2 composite powder was sprayed onto the surface of the wear-resistant ceramic layer using LVCS with a spraying thickness of 80 μm. During the spraying process, the substrate temperature was controlled to be <140 °C. The content of BaF2 in the YSZ-BaF2 composite powder was 20 wt%, and the content of YSZ was 80 wt%. Among them, the BaF2 micro powder (D50=12 μm) was coated with a 3 μm thick YSZ shell layer by the sol-gel method, with a coating rate of 92%. The specific coating process was as follows: BaF2 micro powder was used as the core, and it was impregnated and gelled in an alcohol solution of ZrOCl2·8H2O and Y(NO3)3·6H2O. After sintering at 550 °C, a YSZ shell layer was formed on the surface of the BaF2 micro powder, and the composite powder of YSZ coated with BaF2 was obtained.

[0035] (6) Post-treatment with BaF2 The coated rotor ring was placed in a vacuum impregnation furnace. The impregnating agent was a suspension formed by mixing BaF2-CaF2 eutectic powder and ethanol. The eutectic mass ratio of BaF2 to CaF2 in the BaF2-CaF2 eutectic powder was 62:38, the particle size was 15 μm, and the solid content of the suspension was 35%. The vacuum degree was controlled at 5 × 10⁻⁶. - ² Pa, impregnated for 30 min under ultrasonic assistance; after impregnation, under vacuum conditions (vacuum degree 10). -Sintering was carried out at 120°C for 2 hours at a temperature of 820 °C and a heating rate of 120 °C / h to melt BaF2-CaF2 and fill the pores of the YSZ coating. After sintering, the furnace was cooled to room temperature, and the coating surface was polished to achieve a surface roughness Ra=0.6 μm. The coating was then sealed with an organosilicon resin sealant and cured at 90 °C for 3 hours to improve its corrosion resistance.

[0036] Example 2 The difference between this embodiment and Embodiment 1 is that: In step (2), the thickness of the adhesive layer sprayed is 80 μm.

[0037] In step (3), the gradient transition layer consists of three sublayers, each 60 μm thick, for a total thickness of 180 μm: Sublayer 1: NiCrAlY 80 wt%, Al2O3 20 wt% Sublayer 2: NiCrAlY 50 wt%, Al2O3 50 wt% Sublayer 3: NiCrAlY 20 wt%, Al2O3 80 wt%.

[0038] In step (4), the thickness of the wear-resistant ceramic layer sprayed is 250 μm.

[0039] In step (5), the functional layer coating thickness is 60 μm, the BaF2 content in the YSZ-BaF2 composite powder is 15 wt%, and the YSZ content is 85 wt%. The remaining steps and parameters are the same as in Example 1.

[0040] Example 3 The difference between this embodiment and Embodiment 1 is that: In step (2), the thickness of the adhesive layer sprayed is 120 μm.

[0041] In step (4), the thickness of the wear-resistant ceramic layer sprayed is 350 μm.

[0042] In step (5), the functional layer coating thickness is 100 μm. The BaF2 content in the YSZ-BaF2 composite powder is 25 wt%, and the YSZ content is 75 wt%. The coating structure of the YSZ-BaF2 composite powder is prepared by chemical vapor deposition (CVD). The specific process is as follows: BaF2 micropowder is placed in a fluidized bed reactor with ZrCl4 and YCl3 as precursors and O2 as the reaction gas. Chemical vapor deposition is carried out at 450 °C to form a YSZ shell on the surface of BaF2 micropowder, resulting in a YSZ-coated BaF2 composite powder with a coating thickness of about 2.5 μm and a coating rate of 94%. The remaining steps and parameters are the same as in Example 1.

[0043] Comparative Example 1 YSZ-BaF2 coatings were prepared using conventional atmospheric plasma spraying (APS). The YSZ-BaF2 coatings were prepared by simple mechanical mixing without BaF2 post-bleeding treatment. The spraying process parameters were: main gas (Ar) flow rate 40 L / min, auxiliary gas (H2) flow rate 5 L / min, powder feed rate 45 g / min, spraying distance 100 mm, substrate temperature >300 ℃ during spraying, and delamination and blistering of the CFRP substrate occurred.

[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that the NiCrAlY-Al2O3 gradient transition layer in step (2) is not set, but the Al2O3-TiO2 wear-resistant ceramic layer is directly sprayed onto the surface of the pretreated CFRP substrate. The remaining steps are the same as in Example 1.

[0045] Performance testing: (1) Coating thickness The total thickness of the coating was measured using an eddy current thickness gauge. Figure 1 The diagram shows the spraying structure of Example 1. The total coating thickness is 680 μm, and the thickness of each sublayer is uniform with a deviation within ±5%, which meets the design requirements for the rotor ring coating thickness. In Comparative Example 1, due to severe thermal damage to the substrate, the coating in some areas blistered and delaminated, and the thickness distribution was extremely uneven.

[0046] (2) Bond strength The test was conducted according to ASTM C633 standard, using the dual specimen tensile method. The coated specimen was bonded to the loading fixture and then placed on a universal testing machine with a loading rate of 1 mm / min. The maximum tensile load when the coating separated from the substrate was recorded, and the bond strength was obtained by dividing the load by the coating area.

[0047] The bonding strength of Example 1 was 48 MPa. During the test, the adhesive layer experienced cohesive failure, and no peeling was observed between the coating body and the substrate. Example 2 showed a bonding strength of 42 MPa, and Example 3 showed a bonding strength of 45 MPa. The bonding strength of Comparative Example 1 (traditional APS) was only 12 MPa, and the bonding strength of Comparative Example 2 (without a gradient transition layer) was only 18 MPa. This invention effectively alleviates the thermal expansion mismatch between YSZ and CFRP through a NiCrAlY-Al2O3 composition gradient transition layer. The bonding strength is 3-4 times higher than that of the traditional APS process and about 2.7 times higher than that of the solution without a gradient layer.

[0048] (3) Morphological analysis Figure 2(a) shows the cross-sectional morphology of Comparative Example 1. As shown in the figure, A is a large black cavity on the fracture surface, which is an internal defect of the coating and is prone to become a crack source when under stress; B is the flat droplet accumulation structure unique to thermal spray coating, which presents a lamellar layering and is a typical micro-morphology of plasma spraying; C is a blocky object with sharp edges, indicating that the ceramic phase has undergone transgranular brittle fracture; D is an interlayer crack, indicating that the fracture develops along the weak interlayer interface (intergranular or interlayer fracture); E is a small hole or pit left after the particles are pulled out; F is a large irregular blocky object, which may be an incompletely melted powder particle or agglomerate.

[0049] Figure 2 (b) shows the cross-sectional morphology of Example 1. As shown in the figure, compared with (a), the pore size at A is smaller because the higher BaF2 in the LVCS spraying reduces the large pores and makes the structure more compact. The interlayer bonding at B is improved due to the fluxing effect of BaF2. The number of small pores at E is reduced compared with the APS spraying method. The particle size at F is relatively uniform, indicating that BaF2 refines the grains or improves the droplet spreading.

[0050] (4) Porosity Porosity testing employs image analysis, utilizing ImageJ image analysis software for grayscale thresholding. Porosity is calculated by statistically analyzing the ratio of total pore area to the total analyzed area. Porosity = (Total pore area / Total image area) × 100% The porosity of Example 1 is 6.5%, while the porosity of YSZ coatings prepared by conventional APS process is typically 5-15%, and the porosity of Comparative Example 1 is 13.2%. The porosity of the LVCS process in this patent is significantly lower than that of the APS process. The mechanism of porosity reduction is as follows: in the LVCS process, particles impact the matrix at supersonic speeds, converting kinetic energy into deformation energy, resulting in denser interparticle bonding; the post-diffusion BaF2-CaF2 eutectic melts during sintering at 800-850 °C, and under the action of capillary force, it penetrates and fills the open pores in the coating, further reducing the porosity. A lower porosity (<8%) means that the coating has higher density, which can effectively block the penetration path of corrosive media and reduce stress concentration points. This is of great significance for improving the corrosion resistance and thermal shock resistance of the coating.

[0051] (5) Hardness According to ASTM E384 standard, Vickers hardness tester was used. A diamond square pyramid indenter with a 136° included angle was vertically pressed into the coating surface under a load of 1 kgf. After holding the load for 15 seconds, the load was unloaded. The lengths of the two diagonals of the indentation were measured and the hardness value was calculated according to the formula HV=1.8544×P / d².

[0052] The hardness of Example 1 was HV 920 (load 1kg), while the hardness of the YSZ coating prepared by the conventional APS process in Comparative Example 1 was HV 650 (load 1kg). The hardness of the LVCS process of this patent is significantly better than that of the conventional APS process, increasing by about 42% compared to Comparative Example 1. In the LVCS process, particles impact the substrate at supersonic speeds, converting kinetic energy into deformation energy, resulting in high coating density and low porosity (porosity of only 6.5% in Example 1 and 13.2% in Comparative Example 1), and tighter interparticle bonding. The 800-850℃ sintering treatment after BaF2-CaF2 eutectic infiltration further promotes coating densification. The gradient transition layer effectively alleviates thermal expansion mismatch and reduces defects such as microcracks. In contrast, the conventional APS flame temperature is extremely high (>8000℃), and the molten particles cool rapidly after impacting the substrate, easily forming more pores and microcracks in the coating, resulting in lower hardness.

[0053] (6) Coefficient of friction The friction and wear test was conducted using a ball-and-disc friction and wear testing machine in accordance with ASTM G99 standard. The mating parts were Si3N4 balls (6 mm in diameter), the test load was 5-10 N, and the sliding speed was 0.5 m / s. The test temperatures were room temperature, 200 ℃, 400 ℃, and 500 ℃, with each temperature point tested for 30 min. The steady-state friction coefficient was recorded, and the minimum and maximum values ​​at each temperature were taken as the range of friction coefficients.

[0054] The friction coefficient of Example 1 is 0.10-0.22 in the range of room temperature to 500 °C, the friction coefficient of Example 3 is 0.08-0.18, and the friction coefficient of Comparative Example 1 is 0.30-0.50, which are much higher than those of this patent. The reason why the coating of this patent maintains a low friction coefficient in a wide temperature range is that: in the range of room temperature to 300 °C, the BaF2 particles uniformly distributed in the coating reduce shear resistance through the micro-ball bearing effect; above 400 °C, the BaF2-CaF2 eutectic undergoes a brittle-plastic transformation, and under the action of frictional heat and pressure, it spreads on the coating surface to form a continuous low-shear lubricating film, which transforms the sliding interface into shear slip inside the lubricating film, thereby significantly reducing friction resistance. However, due to the large amount of BaF2 volatilization during the high-temperature spraying process, the actual BaF2 content in the APS coating is severely insufficient, making it impossible to form an effective lubricating film. As a result, the friction coefficient is high throughout the entire temperature range. This invention improves the BaF2 retention rate to over 87% through a triple BaF2 retention strategy, providing a sufficient material basis for the lubrication mechanism, thereby achieving stable low friction over a wide temperature range.

[0055] (7) Wear rate After the above ASTM G99 friction and wear test is completed, the wear area is scanned using a three-dimensional white light interferometer, and the wear volume V (mm³) is measured. The wear rate K is calculated using the following formula: K = V / (F × s) Example 1 is 3.5 × 10 -6 mm³ / N·m, Comparative Example 1: The YSZ-BaF2 coating prepared by conventional APS process has a wear rate of 2×10⁻⁶ mm³ / N·m due to the large amount of BaF2 volatilization, high porosity, and low hardness. -5 The wear rate of the coating of this invention is lower than that of conventional APS by mm³ / N·m. The mechanism is as follows: the high-density coating formed by the LVCS process effectively reduces the entry point of abrasive particles and fatigue spalling sources, and the high hardness gives the coating stronger scratch resistance and cutting resistance; the vacuum impregnation process fills the pores of the coating, further improving the cohesive strength of the coating; the transfer film formed by the BaF2-CaF2 self-lubricating phase during the friction process effectively reduces the interfacial shear stress and reduces the amount of material removed. The low wear rate provides a guarantee for the dimensional stability of the rotor ring and the durability of the coating during long-term operation.

[0056] (8) Actual BaF2 content The actual BaF2 content in the coating was determined by SEM-EDS quantitative analysis. The coating samples were cold-mounted, ground, polished, and then carbon-sprayed. Under a field emission scanning electron microscope equipped with an energy dispersive spectroscopy (EDS) instrument, five fields of view were randomly selected on the YSZ-BaF2 functional layer, and energy dispersive spectroscopy spectra were collected from three micro-area points in each field of view (corresponding to…). Figure 3 The EDS energy spectrum and surface distribution are shown below. The accelerating voltage was 15 kV, and the activity time was 120 s. The mass percentages of elements such as Ba, F, Zr, Y, and O were obtained after ZAF correction. Assuming that Ba and F exist entirely in the form of BaF2, BaF2 = Ba / 0.7833 was converted to the mass fraction of BaF2 compound, and the average value of 15 micro-regions was taken.

[0057] Figure 3 (a), (b), (c), and (d) are EDS element surface distribution diagrams of the wear track region, showing the spatial uniformity of Al, Y, Ba, and F elements within the wear track.

[0058] Figure 3(e) EDS quantitative results of the wear track surface. O, F, Y, Zr, and Ba were detected, where Zr and Y came from the YSZ matrix, Ba and F came from the added BaF2 lubricating phase, and O came from the matrix oxide and surface oxide. In Example 1, the designed BaF2 content was 20 wt%, and the EDS measured Ba element mass fraction was 14.26%, which translates to an actual BaF2 content of 14.26% / 0.7833 = 18.2 wt%, with a retention rate of 18.2 / 20.0 × 100% = 91%. In Example 2, the measured Ba element mass fraction was 10.26%, which translates to an actual BaF2 content of 13.1 wt%, with a retention rate of 87%. In Example 3, the measured Ba element mass fraction was 17.86%, which translates to an actual BaF2 content of 22.8 wt%, with a retention rate of 91%. Comparative Example 1 (APS) showed a measured Ba element mass fraction of only 7.05%, which translates to an actual BaF2 content of 9.0 wt%, resulting in a retention rate of only 45%. This result indicates significant BaF2 volatilization loss during the high-temperature spraying process of traditional APS. However, this invention employs a triple BaF2 retention strategy: "YSZ-coated core-shell structure to suppress spraying volatilization + LVCS low-temperature spraying to reduce thermal volatilization + vacuum impregnation followed by lubrication phase replenishment," thereby increasing the BaF2 retention rate from less than 50% in existing technologies to over 87%.

[0059] (9) Thermal shock cycle The test was conducted in accordance with the HB 7268-96 standard. The coating sample was placed in a muffle furnace heated to 500 ℃ and kept at that temperature for 10 min. It was then quickly removed and immersed in room temperature (about 25 ℃) water to cool. After drying, the surface morphology of the coating was observed. The above cycle was repeated, and the number of cycles when the first peeling with a diameter >1 mm or a crack with a length >2 mm appeared was recorded.

[0060] Example 1 showed no peeling after 68 cycles, Example 2 after 55 cycles, and Example 3 after 72 cycles. Comparative Example 1 (APS) peeled off after only 3 cycles; Comparative Example 2 (without gradient transition layer) peeled off after only 8 cycles. The excellent thermal shock resistance of the coating of the present invention is due to the effective mitigation of the thermal expansion mismatch between YSZ and CFRP by the gradient transition layer. At the same time, the low porosity reduces the thermal stress concentration points, significantly extending the thermal cycle life of the coating.

[0061] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A YSZ-BaF2 self-lubricating ceramic coating on the surface of a rotor ring, characterized in that, From the inside out, the following are included: Adhesive layer: NiCrAlY; Gradient transition layer: NiCrAlY-Al2O3; Wear-resistant ceramic layer: Al2O3-13%TiO2; Functional layer: YSZ-BaF2.

2. The YSZ-BaF2 self-lubricating ceramic coating on the rotor ring surface according to claim 1, characterized in that, The thickness of the adhesive layer is 0.08-0.12 mm; the thickness of the gradient transition layer is 0.15-0.25 mm; the thickness of the wear-resistant ceramic layer is 0.25-0.35 mm; and the thickness of the functional layer is 0.05-0.10 mm.

3. A method for preparing a YSZ-BaF2 self-lubricating ceramic coating on the rotor ring surface as described in claim 1 or 2, characterized in that, The preparation method comprises the following steps: (1) Pre-treat the outer surface of the rotor ring; (2) Adhesive layer spraying: NiCrAlY is sprayed onto the surface of the rotor ring after the pretreatment in step (1); (3) Gradient transition layer spraying: NiCrAlY-Al2O3 is sprayed onto the surface of the adhesive layer described in step (2); (4) Spraying of wear-resistant ceramic layer: Spraying Al2O3-13%TiO2 onto the surface of the gradient transition layer described in step (3); (5) Functional layer spraying: YSZ-BaF2 composite powder is sprayed onto the surface of the wear-resistant ceramic layer described in step (4); (6) Post-treatment with BaF2: After vacuum impregnation of the rotor ring after spraying in step (5), sintering, cooling and polishing, and sealing treatment.

4. The preparation method according to claim 3, characterized in that, The spraying process in steps (2), (3), (4), and (5) all adopts supersonic spraying with a spraying temperature of <150 ℃.

5. The preparation method according to claim 3, characterized in that, In step (3), the gradient transition layer includes 3-5 sublayers. The NiCrAlY content gradually changes from 80-90 wt% near the substrate to 10-20 wt% near the surface along the coating thickness direction. The NiCrAlY content change gradient between adjacent sublayers is 15-25 wt%. The substrate temperature during spraying is <120 ℃.

6. The preparation method according to claim 3, characterized in that, In step (4), the substrate temperature during the spraying process is <130 °C; in step (5), the YSZ-BaF2 composite powder is prepared by sol-gel method or chemical vapor deposition method, and the substrate temperature is controlled to <150 °C during the spraying process.

7. The preparation method according to claim 6, characterized in that, The sol-gel method employs the following approach: (1) Using BaF2 micro powder as the core, it was impregnated and gelled in an alcoholic solution of ZrOCl2·8H2O and Y(NO3)3·6H2O; (2) After sintering at 500-600 ℃, a YSZ shell layer is formed on the surface of BaF2 micro powder to obtain composite powder of YSZ coated BaF2.

8. The preparation method according to claim 6, characterized in that, The chemical vapor deposition method employed is as follows: (1) Using BaF2 micro powder as the core, ZrCl4 and YCl3 as precursors, and O2 as the reaction gas, chemical vapor deposition was carried out at 400-500 °C; (2) A YSZ shell is formed on the surface of BaF2 micro powder to obtain a composite powder of BaF2 coated with YSZ.

9. The preparation method according to claim 3, characterized in that, In step (6), the impregnation agent is a suspension formed by mixing BaF2-CaF2 eutectic powder and ethanol. The mass ratio of BaF2 to CaF2 in the BaF2-CaF2 eutectic powder is 62:38, the particle size is 10-20 μm, and the solid content of the suspension is 30-40%.

10. The preparation method according to claim 3, characterized in that, The sintering in step (6) is carried out under a vacuum or argon protective atmosphere, with a sintering temperature of 800-850 ℃ and a heating rate of 100-150 ℃ / h; the sealing is done with organosilicon resin or polysiloxane, which is cured at 80-100 ℃ for 2-4 h.